Technology Pedagogical Content Knowledge-based learning model in Citizenship Education courses - Dahnial, Irfan; Hasibuan, Selamat Husni; Nasution, Dewi Kesuma; Daniela, Izabela Radu (Universitas Negeri Yogyakarta, 2023)
This study aims to see the readiness of each educator in using knowledge-based learning models of technological pedagogic content in Civics learning. In this case, educators and lecturers play an important role in controlling the learning situation of technology pedagogic content knowledge, researchers consider one of the most effective learning models to be TPACK. In this study, researchers used quantitative research methods to measure the extent to which the learning model influenced knowledge of technological pedagogic content and the readiness of students to carry out learning in the classroom environment. The results of the study show that the TPACK model is very effective in the learning process, especially in Civics subjects, that incorporating TPACK into teacher preparation and professional development programs can lead to improved teaching practices and student learning outcomes. TPACK has become an increasingly important framework in education, as technology continues to play a greater role in teaching and learning.